USING NEWSPAPER IN THE TEACHING OF WRITING NEWS ITEM - Sri Wardani (UMBanjarmasin, 2019)
Writing, one of productive skills, is considered difficult that is why the students get difficulties in getting ideas and arranging them in coherent and cohesive paragraphs; besides that they have lack of vocabularies to express their ideas. This fact is the contrary to the Senior High School Curriculum which states that writing is one of the productive skills has to be covered, such as News Item text. The purpose of this paper is to find out how well newspapers give contribution in teaching News Item text. The design of the research is classroom action research. There were 27 students participated in this research. Test and observation are two main instruments. The results show that using newspaper can improve students’ ability in writing news item text. The data collected from observation indicated that the students were active during the lesson.